Risk of Cardiovascular Disease in Individuals With Nonobese Nonalcoholic Fatty Liver Disease - Ashwini Arvind; Jacqueline B. Henson; Stephanie A. Osganian; Cheryl Nath; Lara M. Steinhagen; Zoe N. Memel; Arley Donovan; Oluwafemi Balogun; Raymond T. Chung; Tracey G. Simon; Kathleen E. Corey (Hepatology Communications, 2022)
Nonalcoholic fatty liver disease (NAFLD) is independently associated with obesity and cardiovascular disease (CVD). CVD is the primary cause of mortality in the predominantly obese population of adults with NAFLD. NAFLD is increasingly seen in individuals who are lean and overweight (i.e., nonobese), but it is unclear whether their risk of CVD is comparable to those with NAFLD and obesity. Using a prospective cohort of patients with NAFLD, we compared the prevalence and incidence of CVD in individuals with and without obesity. NAFLD was diagnosed by biopsy or imaging after excluding other chronic liver disease etiologies. Logistic regression was used to compare the odds of baseline CVD by obesity status. Cox proportional hazards regression was used to evaluate obesity as a predictor of incident CVD and to identify predictors of CVD in subjects with and without obesity. At baseline, adults with obesity had a higher prevalence of CVD compared to those without obesity (12.0% vs. 5.0%, P = 0.02). During follow‐up, however, obesity did not predict incident CVD (hazard ratio [HR], 1.24; 95% confidence interval [CI], 0.69‐2.22) or other metabolic diseases. Findings were consistent when considering body mass index as a continuous variable and after excluding subjects who were overweight. Age (adjusted HR [aHR], 1.05; 95% CI, 1.03‐1.08), smoking (aHR, 4.61; 95% CI, 1.89‐11.22), and decreased low‐density lipoprotein levels (aHR, 0.98; 95% CI, 0.96‐1.00) independently predicted incident CVD in the entire cohort, in subjects with obesity, and in those without obesity, respectively. Conclusion: Individuals with overweight or lean NAFLD are not protected from incident CVD compared to those with NAFLD and obesity, although CVD predictors appear to vary between these groups. Patients without obesity also should undergo rigorous risk stratification and treatment.